Pemanfaatan Limbah Sekam Padi untuk Campuran Pupuk Bokashi dan Pembuatan Biobriket sebagai Bahan Bakar Nabati - Noor Mirad Sari; Lusyiani Lusyiani; Khairun Nisa; Muhammad Faisal Mahdie; Diana Ulfah (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2017)
The rice husk waste often becomes a problem for people in Tatah Makmur district. The mountainous of a stack of rice husk has not been utilized by farmers as a useful material. The science activities for the people aimed to provide knowledge about the utilization of rice husk waste into a charcoal husk, biobricket, and bokashi. The target people of this program are Kelompok Tani Bina Desa Jaya RT. 07 and Yasinan Group RT. 06 in Tatah Makmur district. The types of outcomes generated through the science activities of the people are biobricket and bokashi. The socialization, counseling, and training activities were held from May to October 2015 in Pemangkih Village, Tatah Makmur district, South Kalimantan. The people in the village enthusiastically participated in extension activities as they gained knowledge about the making of bokashi and biobricket so that it can reduce dependence on chemical fertilizers and wood fuels. The science activities for this people can solve the problems of the farmers in the utilization of rice husk waste and at the same time can overcome the farmers’ difficulties in obtaining organic fertilizer.